Antibody response and self-reported adverse reactions following vaccination with Comirnaty: a pilot study from a Croatian university hospital. Issue 11 (15th September 2021) - Lapić, Ivana; Rogić, Dunja; Šegulja, Dragana; Zaninović, Ljiljana
Abstract : This study aimed to determine antibody responses against SARS-CoV-2 spike (S) after both BioNTech–Pfizer Comirnaty vaccine doses and study the correlation with self-perceived adverse reactions. Antibodies determination with Elecsys anti-SARS-CoV-2 S assay was performed a day prior to or just before administration of the second dose and 8–13 days after the second dose. Participants selected from a predefined list of the experienced local (injection site reactions) and/or systemic (fatigue, headache, myalgia, arthralgia, chills and fever) post-vaccination adverse reactions. An average 100-fold increase in antibody titre in naive vaccinees was observed between the two time points (median 67 U/mL vs 2841 U/mL, p<0.001). Participants aged below 50 had higher antibody titres (median 99 U/mL vs 26 U/mL, p=0.003 after the first dose; median 3617 U/mL vs 2556 U/mL, p=0.026 after the second dose). All reported adverse reactions were mild-to-moderate, with more participants declaring systemic reactions after the second dose (p=0.001), without a clear correlation with antibody titre.